This equals 3x+3 also written as 3(x+1). If you mean a linear equation like 3x + 3 = 0, then the solution is x = -1
Chat with our AI personalities
Here,x+2x+3=?
Now,
X+2x=-3
Or,3x=-3 (1x+2x)
Or,x=-3÷3
Or,x=-1
Therefore,X=-1
2x2 + 7x + 6 = 2x2 + 4x + 3x + 6 = 2x(x + 2) + 3(x + 2) = (x + 2)(2x + 3)
x + 3 + 2x = x + 9 x + 2x + 3 = x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 2x + 3 = 9 2x + 3 - 3 = 9 - 3 2x + 3 - 3 = 9 - 3 2x = 9 -3 2x = 6 2x/2 = 6/2 2x/2 = 6/2 x = 6/2 x = 3
(x + 3)(x - 1)
2x + 3 = x + 1 Subtract x from both sides: x + 3 = 1 Subtract 3 from both sides: x = -2
x(2x - 3)(x + 4)